Analisis Pengendalian Kualitas pada Proses Produksi dengan Menggunakan Metode FMEA (Failure Mode and Effect Analysis) di PT XYZ - Bayu Dwiyanto Firmansyah; Adi Fitra; Rudy Effendi Listyanto (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
PT XYZ is a company engaged in the automotive component sector, namely producing car AC (Air Conditioning) compressors as its main product. PT XYZ often experiences problems in fulfilling consumer needs, because there are products produced that are still Not Good (NG). This study aims to be able to carry out quality control in the production process and can prevent the level of product defects during the production process. Then this study also identifies what causes defects in products for product quality control at PT XYZ in order to control and minimize the level of defects and can produce products that have high quality standards. The method used in this study is Failure Mode and Effect Analysis (FMEA). The results of this study, the largest RPN value is a product that is a deep scratch on the surface of the front or rear cylinder with an RPN value of 100 factors that cause dent defects with many chips in the machine, the product looks like there are some fairly deep chips on the surface of the front or rear cylinder RPN value 60 is a chip defect, this is caused by employees being less careful when the product comes out of the machine, the product has a point in the gaps between the holes of the Cylinder product RPN value 45 is a porosity defect, this is caused by obstacles in the machine that is not repaired and not maintained, so that during the production process there are obstacles to defects in the product caused by the machine. Of the several causes above that can affect quality, including the machine still leaving a lot of chips, then the lack of monitoring and control of production operator employees, and not doing maintenance.